Penerapan Metode Prototype pada Sistem Pemesanan Jasa dan Produk Berbasis Mobile Sebagai Upaya Untuk Meningkatkan dan Memperluas Jangkauan Layanan - Hendrawan, Fauzi Bayu; Mahardika, Fathoni; Santika, Deris (Fakultas Teknik Universitas Hamzanwadi, 2024)
The rapid development of science and technology has had a significant impact on various aspects of life, including the way people carry out their daily activities. Beauty salons are now not only the domain of women but also in demand by men so that customer satisfaction is increasingly prioritized. To improve service and operational efficiency, an Android-based booking application was designed that allows customers to make reservations without having to come directly to the salon. The use of this application aims to minimize time and facilitate the management of transactions and customer data by the salon. This booking application was built using a prototype method that allows iterative application development based on user feedback. This method was chosen to ensure that the application can better meet user needs and be adjusted based on input received during the development process. The result of this research is a booking application that makes it easy for users to order services and products online anytime and anywhere, and helps Ellma Salon manage customer and order data more efficiently. This application is expected to be an effective solution to the problems faced by Ellma Salon, increase customer satisfaction, and expand the range of salon services